Implementasi Andragogi Platform E-learning pada Blended Learning di Universitas Negeri Padang - Rahmat, Imran; Ridwan, Ridwan (Journal of Education Technology, 2020)
The background of this research was blended learning on adult education especially on the design used in the online platform because blended learning was a learning model that combines face to face learning and online learning activities. This research was a descriptive research by using qualitative method; the data was collected by observation and interview methods. The subject of this research was the history of modern thinking course, study program on Visual Communication Design, Padang University which has used blended learning in the learning process. Data analysis was performed by using the Bogdan & Biklen model. The results showed that the e-learning used in the history of modern thinking course, study program on Visual Communication Design, Padang University was still not optimal to fulfil the adult learning needs, it wass expected that UNP (Padang University) could add and optimize the e-learning features in the future to make it more optimal.